ECG Quiz no. 26 - Okreglicki, A (SA Heart Journal, 2017)
A 69 year-old man was referred for a “pre-op” cardiological opinion. He had been admitted to the surgical ward and was due for elective oesophagoscopy under general anaesthetic for dysphagia. The concern of the surgeon and anaesthetist was the bradycardia during routine pre-procedure assessment.